At first sight or second glance: clinical presentation of mosaic manifestations of autosomal dominant skin disorders : a case series - Toberer, Ferdinand; Schneiderbauer, Roland; Haußer-Siller, Ingrid; Kröhl, Verena; Epple, Andreas; Moog, Ute; Enk, Alexander; Lonsdorf, Anke Susanne (Journal of the European Academy of Dermatology and Venereology, 2017)
Background: Several autosomal dominant disorders may manifest in mosaic patterns with cutaneous involvement. Genomic mosaicism results from postzygotic autosomal mutations, giving rise to clonal proliferation of two genetically distinct cell groups, which clinically present as lesions following the lines of Blaschko. Objective: To increase the awareness of the clinical variability of mosaic manifestations in autosomal dominant skin disorders in order to avoid delayed diagnosis. Methods: Clinicopathologic correlation in a case series including three patients with mosaic manifestations of different autosomal dominant skin diseases. Results: Here, we describe a patient with type 1 segmental mosaicism of epidermolytic ichthyosis (case 1) and two patients with either type 1 (case 2) or type 2 (case 3) segmental neurofibromatosis 1 (NF1). Conclusion: Dermatologists should be familiar with mosaic manifestations of autosomal dominant skin diseases to ensure appropriate guidance of the affected patient. Genetic counselling is mandatory as even limited forms of mosaicism may involve the patient's germline with a moderately increased risk to transmit the mutation to their offspring, resulting in a more severe, generalized form of the respective disease.
First published: 25 March 2017
Gesehen am 25.06.2018